Dissociative Fugue: A Case Report - Valadas, Maria Teresa (2021)
A dissociative fugue occurs when an individual with dissociative amnesia wanders away from their familiar surroundings, maintaining self‑care and apparently normal behavior to observers, lasting from hours to months in a row. New identities can be assumed and even organized travel can occur. While dissociative amnesia by itself may have a prevalence of around 7.2%, dissociative fugue is a rare entity, with unknown prevalence, and there are few reports in the literature. In this article, we describe a case of dissociative fugue in a 34‑year old woman that lasted eight months. Dissociative amnesia with fugue remains an interesting topic for further research since it can present a diagnostic challenge, there are currently no evidence‑based pharmacological treatments and prognosis varies greatly between patients.